TOWARDS A CONCEPTUAL MODELLING OF TRANSFORMATIONAL LEADERSHIP - Zacharis, Konstantinos (IJRDO - Journal of Applied Management Science, 2016)
Modern educational systems are organized around patterns of leadership, which isconsidered a crucial element for their existence and cope with future change. In thecurrent study, the new roles of leadership in contemporary education organizations arebeing asserted. Nowadays, the demands for a transformational-type of leadershipinside a highly effective steering pattern are rising. At the same time, the need toincorporate ICT into the upper level functions of the hierarchy is obvious.What are the specific traits a leader has to possess in order to manage successfully aneducational organization? What is principle-centered leadership and why is itappropriate for school principals? How can a novel leadership scenario fosterinnovation and performance and at the same time liberate schools from the tyranny offormal learning? What is the role of ICT artifacts along that process?The new generation of school leaders is called to answer these questionsconvincingly. To this aim, it has to redesign a cohesive vision based on studentachievement and collaboration, to align all available resources (including curriculum,instruction and assessment). At the same time it should respect cooperate culture,sustain sub-systems, manage budgets, promote capacity learning and tune the wholestructure towards excellence and high performance. This does sound, surely, as achallenging task.